Kepastian hukum terhadap pemenang lelang dalam lelang agunan bank (Studi Kasus pada Putusan Nomor 193/PDT.G/2019/PN.PTK) - Nurhayati M Sinaga; Sutiarnoto Sutiarnoto; Jelly Leviza; Affila Affila (Fakultas Hukum Universitas Al Azhar Medan, 2023)
Using common violations, the Law on Liability gives the creditor the privilege of executing the object in his power. Furthermore, repayment of receivables is taken from the proceeds of the auction with priority rights from other creditors. Through Pirate Execution based on the executory title stated in the Certificate of Dependent Rights Following the provisions of Article 11 paragraph (2) letter KUUHT, APHT stipulates the emptying of the object of the dependent right at the time of execution of the dependent right, so that the debtor is obliged to follow the auction decision and has no reason to refuse the emptying. In the Universal People's Credit Bank, there was a conflict because the debtor did not pay the receivables following the previous agreement. As a result, the creditor, the Universal People's Credit Bank in Pontianak, executed the guarantee through a public auction. However, the debtor made legal efforts to oppose (verzet), and the debtor filed an objection in case No.193/Pdt.G/2019/PN. Ptk.The winner of the auction cannot reverse the name or control the auction results. This study used a normative jurisprudence law approach. This method deals with problems by studying the provisions of applicable laws and regulations. The focus of this study is descriptive analysis. Therefore, the decision of civil case No. 193/Pdt.G/2019/PN.Ptk, Deed of Auction Minutes No. 492/53/2020, Law No. 10 of 1998, Law on Dependent Rights No. 4 of 1996, Basic Agrarian Law No. 5 of 1960, and Minister of Finance Regulation No. 213/PMK.06/2020 concerning Technical Guidelines for Auction Implementation are the subjects of this study. The research reveals the efforts of the block applicant and the Land Office to file an Unlawful Action lawsuit with the Court to remove the block as legal protection for the auction winner. The winner of the auction can also ask the District Court to stop the auction object. In decision number 193/Pdt.G/2019/PN.Ptk, the Panel of Judges stated that the object of the dependent rights used by the Plaintiff as collateral has the same executory power as a court decision that has permanent legal force. Under the executory title, an execution auction can be conducted directly, and the debtor must leave or vacate the property of the lien. Because it has violated the civil rights of others, the plaintiff's actions are included in the category of unlawful actions. To avoid juridical obstacles, the government should be able to amend and add clauses in the UUHT by giving authority or directly appointing bailiffs and police officers to execute collateral emptying as evidenced by the deed of auction minutes to ensure legal certainty in the process of execution of dependent rights. Thus, KPKNL and the Bank can synergize with these rules by carrying out auction execution procedures